Long‐Term Influence of Electrode Array Length on Speech Recognition in Cochlear Implant Users. (1st August 2020) - Canfarotta, Michael W.; Dillon, Margaret T.; Buchman, Craig A.; Buss, Emily; O'Connell, Brendan P.; Rooth, Meredith A.; King, English R.; Pillsbury, Harold C.; Adunka, Oliver F.; Brown, Kevin D.
Abstract : Objectives/Hypothesis: Results from a prospective trial demonstrated better speech recognition for cochlear implant (CI) recipients implanted with a long lateral wall electrode array compared to subjects with a short array after 1 year of listening experience. As short array recipients may require an extended adaptation period, this study investigated whether differences in speech recognition continued through 4 years of CI use. Study Design: Long‐term follow‐up of a prospective randomized trial. Methods: Subjects were randomized to receive a MED‐EL medium (24 mm) or standard (31.5 mm) array. Linear mixed models compared speech recognition between cohorts with word recognition in quiet and sentence recognition in noise at 1, 3, 6, 12, 24, and 48 months postactivation. Postoperative imaging and electric frequency filters were reviewed to assess the influence of frequency‐to‐place mismatch and angular separation between neighboring contacts, a metric associated with peripheral spectral selectivity. Results: Long (31.5 mm) array recipients demonstrated superior speech recognition out to 4 years postactivation. There was a significant effect of angular separation between contacts, with more closely spaced contacts associated with poorer speech recognition. There was no significant effect of mismatch, yet this may have been obscured by changes in frequency filters over time. Conclusions: Conventional MED‐EL CI recipients implanted with 31.5‐mm arrays experience better speech recognition than 24‐mm array recipients, initially and with long‐term listening experience. The benefit conferred by longer arrays in the present cohort can be partially attributed to more widely spaced electrode contacts, presumably a result of reduced channel interaction. Level of Evidence: 2 Laryngoscope, 131:892–897, 2021